Digital Marketing Strategy to Increase Customer Income of Savings and Loan Cooperatives - Muh. Nur Ali Khoirun Nasikin; Via Hidahyatul K; Zuly Safitri; Ahmad Nurfaid; Have Zulkarnaen (Research Parks Publishing LLC, 2026)
This study aims to analyze digital marketing strategies implemented to increase customer retention and identify supporting and inhibiting factors in their implementation. In the digital era, developments in information technology have changed communication and interaction patterns between financial institutions and customers. This study employed a qualitative research method with participant observation. The data collection method applied in this study included two approaches: literature research and field study. The literature study was conducted by examining various literature sources related to the research topic. The results showed that digital marketing strategies implemented through social media, websites, instant messaging applications, and other digital platforms were able to increase the number of customers through easy access to information, speed of service, effective communication, and increased customer engagement. In addition, the use of digital media helped institutions build closer relationships with customers and increased trust in the products and services offered. Supporting factors for the success of digital marketing strategies included technological developments, management support, and high internet usage by the public. Inhibiting factors identified were limited human resources with digital competencies, limited marketing budgets, and low digital literacy among some customers.